2021
DOI: 10.1111/acem.14388
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of prehospital antibiotics for severe sepsis

Abstract: Severe forms of sepsis are major contributors to morbidity and mortality worldwide, with mortality rates as high as 25%-60%. 1 Sepsis with hypotension and septic shock, which we define as sepsis with a systolic blood pressure ≤ 90 mm Hg that is refractory to an initial fluid bolus, 2 are important subsets of sepsis and are medical emergencies for which timeliness of care is crucial. The literature demonstrates that early administration of antibiotics provides a significant mortality benefit in both conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…19,30 Four studies reported the secondary length of stay outcomes (hospital and ICU). 28,30,31,33 The individual study outcomes and results are detailed in Table 5.…”
Section: Outcomes and Results Of Individual Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…19,30 Four studies reported the secondary length of stay outcomes (hospital and ICU). 28,30,31,33 The individual study outcomes and results are detailed in Table 5.…”
Section: Outcomes and Results Of Individual Studiesmentioning
confidence: 99%
“…Five studies reported on mortality, but only one was prospectively statistically powered to this outcome. 34 Three found no difference 19,30,31 whilst two reported statistically significant reductions favouring prehospital antibiotics. 28,33 Regarding 28-day mortality, the RCT by Alam et al 30 reported 8% mortality in both groups, though this time point was not the one to which the study's statistical power was calculated.…”
Section: Mortalitymentioning
confidence: 95%
See 3 more Smart Citations